Estado de la Memoria y la Flexibilidad Cognitiva en Personas Privadas de la Libertad Consumidoras y No Consumidoras de Sustancias Psicoactivas (2023)
The consumption of psychoactive substances (SPA) has become a serious social problem, especially in prison communities that are particularly vulnerable to this challenge. The objective of this research was to establish whether there were statistically significant differences in working memory and cognitive flexibility in incarcerated individuals who consume and not consume psychoactive substances, through the application of neuropsychological instruments.